2009
DOI: 10.1164/rccm.200804-560oc
|View full text |Cite
|
Sign up to set email alerts
|

Airflow Limitation in Smokers Is Associated with Subclinical Atherosclerosis

Abstract: Smokers with airflow limitation had exaggerated subclinical atherosclerosis. This study suggests that middle-aged men who are susceptible to COPD may also be susceptible to vascular atherosclerosis by smoking, and atherosclerotic change starts early in the disease process of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
127
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(149 citation statements)
references
References 42 publications
13
127
3
6
Order By: Relevance
“…The degree of endothelial dysfunction was related to lung function and serum C-reactive protein, providing another inflammatory link between COPD and atherosclerosis. Subclinical atherosclerosis is likely to start early in the course of COPD, as suggested by the findings of increased carotid artery intima-media thickness in middle aged smokers with airflow limitation [20].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…The degree of endothelial dysfunction was related to lung function and serum C-reactive protein, providing another inflammatory link between COPD and atherosclerosis. Subclinical atherosclerosis is likely to start early in the course of COPD, as suggested by the findings of increased carotid artery intima-media thickness in middle aged smokers with airflow limitation [20].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%
“…Similar results were reported by other investigators (38); they found that smoking frequency (pack/year) did not differ between COPD patients with normal CIMT and those with a thickened CIMT. Two other studies reported that CIMT was significantly increased: in smoker COPD patients compared to the smoker control group (37) and in smokers with airflow limitation compared to smokers in the control group and never-smokers in the control group (40). This might be an indication of the influence of other factors leading to intimal thickening other than smoking.…”
Section: Discussionmentioning
confidence: 85%
“…COPD and asthma are conditions with many comorbidities, albeit asthma to a lesser extent than COPD [28][29][30][31]. To date, very limited data have been gathered on the association between asthma and CKD.…”
Section: Discussionmentioning
confidence: 99%